(untitled) (The Journal of Plant Protection Sciences, 2023)
Soybeans [Glycine max L. (Merr.)] are a ma jor source of protein for animal feed and are also an increasingly important component of the diets of consumers. Soybean cyst nema tode (SCN), Heterodera glycines, is the major pest of soybean and over the last decade ac counted for more than 50% of the crop lost to disease. Due to improved crop management and breeding, the loss to SCN decreased to some extent, but it has been remained a great challenge. Therefore, further improvement to control nematode infection is indispensable to reduce the crop losses. Root-knot nematode (RKN, Meloidogyne incognita) is also a pathogen of soybean. Although RKN does not cause as great a loss to the soybean crop as SCN, RKN has a very broad host range and is particularly damaging where soybean is ro tated in with other susceptible crops (1). Comparison of the pathogenicity of the cyst and root-knot nematodes is also needed to create strategies to broaden resistance to nematodes in soybean and other crops.